Student-performed periodontal therapy: retrospective cohort study on outcomes and related recommendations for enhancing undergraduate periodontal education - Herz, Marco Michael; Schamuhn, Judith; Krumm, Boris; Bartha, Valentin (BMC medical education, 2025)
The aim of the study was to evaluate periodontal treatment success in patients treated by undergraduates. The findings shall be used to gain implications for future curriculum frameworks.
Gesehen am 30.11.2025